Urinary extracellular vesicle dynamics in Parkinson's disease patients with urinary dysfunction - Roy, Santanu; Kashyap, Namita N.; Anchan, Abigail Sheldon; Punja, Dhiren; Jasti, Dushyanth Babu; Upadhya, Dinesh (Frontiers in Neurology, 2023)
Parkinson's disease (PD) presents with severe motor manifestations and a plethora of non-motor symptoms. Urinary dysfunctions are one of the most common non-motor symptoms of PD patients responsible for reduced quality of life. Urinary extracellular vesicles (EVs) are mostly considered to originate from the cells in the urogenital tract. In this study, we have performed urinary EV analysis in 29 PD cases with varied severity of urinary dysfunction and correlated it with the EV dynamics in 29 age-matched controls. In the studied cases, apart from urinary dysfunction, symptoms of depression, anxiety, cognitive dysfunction, sleep, and wakefulness were observed in >75% of the cases. No significant difference in urinary EV size, concentration and urinary EV protein concentration was observed between PD cases with urinary dysfunction and controls. However, a significant positive association was observed between urinary EV concentration and motor scores (p = 0.042), while no association was observed between urinary EV concentration and urinary dysfunction scores. Chronic stress induced by motor symptoms could be one of the reasons for excessive EV production in PD patients with urinary dysfunctions. Large-scale studies on the association of urinary EV dynamics with motor and non-motor symptoms may provide additional information on urinary dysfunction in PD.